KARAKTERISTIK MORFOLOGI DAN HABITAT IKAN BREK (BARBONYMUS BALLEROIDES VAL. 1842) DI SUNGAI SERAYU JAWA TENGAH - Hayono, Hayono; Rahadjo, M F; Affandi, Ridwan; Mulyadi, Mulyadi (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTBrek is a consumption fish belong to barbs group that widely distributed, one of them is in Serayu river. The aims of this study was to reveal the characteristics of meristic, morphometric, and habitat of the species. The study was conducted on the Serayu river especially in Banjarnegara, Central Java Province. Sampling was conducted on May 2012 to June 2013. The area of study was divided into three zones and the zones was categorized based on Reservoirs at Mrica area these are upper zone, reservoir zone, and below the reservoir zone. Fishing gear used are cast net, elektorfishing, and gill nets. Samples of fish were caught preserved in 4-10% formalin solution and then observed in the laboratory. Morphometric characters observed were 24 characters. The results were standardized to standard length, then analyzed with discriminant methods. The structure of the scales and number of ridges on the back of the last dorsal fin spines also observed. The results meristic characters are 4.8 dorsal fin, 3.5 anal fin, 1.14-16 pectoral fin, and predorsal 10-13 scales, also there were no spots on the caudal peduncle. The results of discriminant analysis showed known five characters distinguishing three species near 100%. The habitats have rocky bottom, rapid current, and divide into two groups.Keywords: barb fish, meristic, morphometric, Serayu river